Relationship Between High Sensitivity TNF-? WITH clinical outcome During Admission In Acute Ischemic Stroke - Mohammad Saiful Ardhi1 , Mohammad Saiful Islam1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background : Tumor necrosis factor alpha (TNF-?), together with other pro-inflammatory cytokines suchas Interleukin-1b (IL-1b), IL- 6 and IL-8, play a role in the ischemic injury of the central nervous system.TNF-? has adverse effects on ischemic brain tissue. The mechanism generated is a multicomplex process. Inother studies, an increase in TNF-? can actually have neuroprotective effects. This study aims to determinethe relation between the levels of the High Sensitivity TNF-? with clinical outcome in acute ischemic stroke.Method : Thirty patients with acute ischemic stroke patients who admitted in Dr. Soetomo hospital Surabayaduring the period December 2011 to February 2012. 2 cc of vein blood for examination High sensitivityTNF-? was drawn during admission from acute ischemic stroke. Clinical outcome in acute stroke wasmeasured by NIHSS score.Results: From 30 research samples, the mean age of patients was 59.53 ± 11.51 years. The mean HighSensitivity TNF-? level in the study subjects was 2 ± 0.99 pg / ml. NIHSS examination showed the medianvalue of the NIHSS was 5 with a range of 2-19. There is a correlation but not statistically significant withthe strength is very weak between High Sensitivity TNF-? with the NIHSS in patients with acute thromboticstroke (r = 0.100 and p = 0.600).Conclusion: There is relationship between serum levels of High sensitivity TNF-? with clinical outcome inacute ischemic stroke patients.